THE INFLUENCE OF INTELLECTUAL CAPITAL ON FIRM VALUE WITH EARNINGS MANAGEMENT AS A MODERATING VARIABLE: A STUDY IN FINANCIAL SERVICE COMPANIES LISTED ON INDONESIA STOCK EXCHANGE (IDX) - Aulizza Abdul Fanni; Fuad Fuad (JURNAL AKUNTANSI DAN AUDITING, 2019)
This research aims to examine the influence of intellectual capital performance on firm value and the moderating influence of earnings management on the relationship of intellectual capital with firm value in financial service companies listed on the Indonesia Stock Exchange during 2015 – 2018. Based on the population of 90 companies per year, a test of 69 sample companies that met the criteria of purposive sampling was conducted. The panel data regression technique is used to analyze the data. The findings show that intellectual capital provides a significant positive influence on firm value. Most notable contributions came from human capital and relational capital components, but not the structural capital component. This condition is considered good, although not ideal yet. Other findings reveal that earnings management did not moderate the relationship of intellectual capital with firm value.